Language Learning Motivation and L2 Pragmatic Competence - Yang, He. (Singapore : Springer Nature Singapore : Imprint: Springer, 2022)
This book provides comprehensive investigation of the effect of motivation on L2 learners' pragmatic learning, which has been discussed for a long time but remains under-explored. This study examines whether and to what extent learners' levels of motivation influence their pragmatic awareness, comprehension and production in an EFL context. It presents an original study that not only enriches our knowledge of the feasibility of modern technology in collecting large-scale data related to pragmatic competence but also eminently connects L2 pragmatics more closely with mainstream second language acquisition research by focusing on the role of motivation in pragmatic learning. This book will be of great value to researchers and postgraduates interested in second language acquisition, especially those who work on L2 pragmatics and individual variation among learners.
Chapter 1. Introduction -- Chapter 2. Literature Review -- Chapter 3. Methodolog -- Chapter 4. EFL Learners' Motivation for Studying English -- Chapter 5. Pragmatic Awareness and L2 Motivation -- Chapter 6. Pragmatic Comprehension and L2 Motivation -- Chapter 7. Pragmatic Production and L2 Motivation -- Chapter 8. Conclusions.
Keywords: Language and languages-Study and teaching; Applied linguistics; Language Education; Language Teaching and Learning; Applied Linguistics